Differentiated Interactive Media Based on Balinese Folklore: A Solution for Fostering Elementary School Students' Social Attitudes - Wulandari, I Gusti Agung Ayu; Esaputra, I Nyoman Tri; Chiu, Chunta; Haryanti, Yuyun Dwi; Utami, Ketut Herya Darma (Yayasan Keluarga Guru Mandiri, 2026)
This study is inspired by the relevance of positive social attitudes in developing harmonious connections with others, including peers, family, and society. The study examines how differentiated digital media, grounded in Balinese folklore and cultural values, influence the social perspectives of elementary school students. The research method adopted is quantitative, with an experimental component. The study's findings indicate that utilizing digital media rooted in Balinese culture, particularly through folklore, significantly enhances students' social attitudes, including helping one another, empathy, tolerance, peaceful living, and social participation. These improvements are closely tied to the cultural messages embedded in the stories. The results support earlier research that folklore, as a cultural artifact with strong moral messages, can shape future behavior. This study highlights the importance of integrating cultural heritage into digital learning tools to build moral and social values. The recommended steps include producing more culturally-based educational resources, providing teacher training to apply culturally-rich materials, and conducting further studies to evaluate the long-term impact of folklore-based digital media on character education.